Responsibilities of Land Deed Officials In Disputes of Making Deeds of Sale and Purchase of Inherited Land - Srynovia Wati Amu; Nurul Fazri Elfikri (Estudiante Law Journal, 2022)
The purpose of this study is to find out the PPAT's responsibility in making the deed of sale and purchase of jointly owned land rights (boedel) which is in dispute and to find out the efforts of PPAT in completing the deed of sale and purchase of land which is still in the status of joint property rights (boedel). The research method used is sociological juridical, research based on a principle of law or regulation that applies to the reality that occurs in society or in practice as it is. The results of the study found that the PPAT's responsibility was in making the deed of sale and purchase of landShared Property Rights (Boedel) Those Who Are Still Disputingwill not continue in making the deed of sale and purchase when one of them still objected or is still in dispute because it is already contained in the laws and regulations but in other studies will still accept the disputed on the condition that mediation must be carried out so that the problem can be solved and PPAT's efforts in completing the deed of sale and purchase of land common property rights, namely by conducting deliberation.